Private real estate investment : - Brown, Roger J. (Elsevier Academic Press, 2005)
This book is designed as a supplementary text for upper division undergraduate and graduate real estate investment courses. The CD-ROM included with the book contains spreadsheets for data analysis tailored specifically to real estate settings.